Inhibitors and facilitators of compassion‐focused imagery in personality disorder. (18th December 2017) - Naismith, Iona; Mwale, Amanda; Feigenbaum, Janet
Abstract : Background: Compassion‐focused therapy (CFT) has potential to benefit clients with a personality disorder (PD), given the inflated levels of shame and self‐criticism in this population. However, clinical observation indicates that clients with PD may find techniques from this approach challenging. Aims: The aim of this study is to trial one aspect of CFT, compassion‐focused imagery (CFI), with this population, and identify factors that predict clients' ability to generate CFI and experience self‐compassion during the task, including type of CFI exercise and, second, to establish whether CFI outcomes increase with practice. Method: In Study 1, 53 participants with a diagnosis of PD completed measures of self‐compassion, self‐reassurance, shame, self‐criticism, fear of self‐compassion, affect, anxious and avoidant attachment, and mental imagery abilities. Participants were assigned to trial CFI from memory ( n  = 25) or from imagination ( n  = 28), then rated their image's vividness, its compassionate traits, and ease of experiencing compassion. A negative mood manipulation was carried out, and CFI tasks and outcome measures were repeated. For Study 2, self‐compassion and self‐criticism were measured before and after 1 week of daily CFI practice. Results: Study 1 found that negative mood and low mental imagery ability are significant inhibitors to generating compassionate images and affect. The 2 CFI exercises were equally effective. Study 2 suffered from high attrition, but regular practice was associated with significant improvement in self‐compassion (though not self‐criticism). Conclusions: CFI appears to be effective in improving self‐compassion for some clients. However, it is less effective in the presence of negative affect. Clients with low mental imagery ability may benefit more from alternative CFT techniques.